(untitled) (Journal of Global Humanities and Social Sciences, 2025)
With the rapid development of digital technology, the time is ripe for digital technology to be integrated into the protection and transmission of intangible cultural heritage of dragon and lion dance sports (dragon and lion dance). This paper discusses the application paths of digital technology in the protection and dissemination of dragon and lion dance, including the construction of a digital system, the establishment of a digital cultural archive, the construction of a digital display platform, the development of intangible cultural heritage online courses and the promotion of digital innovation. These paths are aimed at accurately recording and preserving dragon and lion dance skills through high-tech means, broadening dissemination channels, enhancing interactive cultural experiences, and promoting international dissemination. The integration of digital technology not only provides a new means for the protection of dragon and lion dance, but also injects new vitality into its inheritance and development, which is of great significance for the promotion of Chinese outstanding traditional culture.